Real-life evidence of encorafenib plus binimetinib in patients with unresectable advanced or metastatic BRAFV600-mutant melanoma in Spain: the BECARE (GEM-2002) trial - Soria, Ainara; Sanchez Mauriño, Pedro; Serrano Domingo, Juan José; García Galindo, Regina; Sequero, Silvia; Gutiérrez Sanz, Lourdes; Crespo, Guillermo; Díaz-Beveridge, Roberto; Puértolas, Teresa; López, Pedro; Fra Rodríguez, Joaquín; López Castro, Rafael; et al. (Frontiers in Oncology, 2025)
PurposeCombined BRAF/MEK inhibition with encorafenib (E) plus binimetinib (B) has demonstrated efficacy and tolerability in phase III clinical trials, and is the standard of care for advanced/metastatic BRAFV600-mutant melanoma. However, real-life evidence is limited, particularly in patients pre-treated with immune checkpoint inhibitors (ICI).Patients and methodsBECARE GEM 2002 was a retrospective, non-interventional study aimed at investigating the real-world effectiveness and tolerability of EB in patients with unresectable or metastatic BRAFV600-mutant melanoma conducted at 21 sites in Spain. The primary objective of this study was to characterise the population of patients receiving EB and assess the efficacy and tolerability of EB in real life. The study included patients treated according to standard clinical practice with EB as the 1st line or 2nd line after progression to ICI for an unresectable or metastatic stage. Patients who previously received treatment with BRAF and/or MEK inhibitor, other than as adjuvants, that ended ≥ 6 m before EB were not eligibleResultsFrom September 2021 to March 2023, 117 patients were included; 89 (76.1%) and 28 (23.9%) patients received EB as 1st line and 2nd line, respectively. The median follow-up was 13.8 months (95% CI: 12.0-17.4). In patients with EB as 1st line treatment, ORR and median PFS were 75% and 12 months (95% CI: 9.4-18.6), respectively. In patients with EB as 2nd line treatment after ICI, ORR and median PFS were 77.8% and 12.5 months (95% CI: 6.6-NA), respectively. In patients with brain metastasis ORR and median PFS were 70.8% and 6.3 months (95% CI: 6.1-10.3). Treatment-related adverse events of grade ≥3 were reported in 17 (14.5%) patients; transaminitis (9.4%) and diarrhoea (2.6%) were the most frequent adverse events.ConclusionIn this real-world study, EB treatment demonstrated effectiveness and a consistent safety profile in patients with BRAFV600-mutant melanoma treated according to standard clinical practice, including in those with prior ICI treatment and of brain metastasis; therefore, EB is a feasible treatment option for unresectable and metastatic melanoma.Clinical trial identification: REec: 0004-2021-OBSClinical trial identificationREec: 0004-2021-OBS.